91.4k views
2 votes
-2(2u-3)+3u=3(u+8)
u=?

User Ramen
by
4.9k points

1 Answer

5 votes
If you expand this equation first
You get -4u+6+3u=3u+24

And if you simplify that you get:
-u+6=3u+24
Now you need to solve this equation to find u

First bring 3u to the other side to -u-3u (the positive changes to negative)
Now the equation is
-4u+6= 24
Take 6 of both sides
-4u=24-6= 18
-4u= 18
So u= -18/4
Which simplifies to -9/2

Answer: -9/2
User Sabella
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.